TRADISI MENYAMBUT KELAHIRAN ANAK “MAMOHOLI” DALAM ADAT MASYARAKAT BATAK TOBA DESA ONANRUNGGU II KECAMATAN SIPAHUTAR KABUPATEN TAPANULI UTARA - Pramita Silitonga; Isjoni Isjoni; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Tradition is everything in the form of customs, habits and beliefs that have been distributed or passed down by the community from generation to generation generations so as to create a tradition that is still to be done. Tradition contained in the village of Onanrunggu II is Mamoholi tradition, this tradition is done by the Batak Toba people to welcome the birth of a child in their family. The purpose of this research is to explain about the tradition of welcoming the birth of children in Toba Batak custom. The author uses historical methods, namely heuristics, interpretation, and historiography, and qualitative methods with data analysis techniques using descriptive qualitative analysis. Based on the research results in the field that in welcoming the birth of a child Batak Toba community in the village of Onanrunggu II perform various rituals or customary activities as a form of thanksgiving to the presence of God Almighty for the birth of a child in one family. Tradition Welcoming the birth of a child called Mamoholi belongs to a great customary celebration because it presents the complete elements of Dalihan Na Tolu(Three of the Furnace),and there are some important processions that must be done in traditional ceremonies to welcome the birth of this Mamoholi child. The ritual performed has a high spiritual meaning in the life of the Batak Toba community and various functions. This tradition has been handed down in the village of Onanrunggu II, and various efforts made by the Batak Toba community in Onanrunggu II village so that this tradition is still implemented. One of them is to impose social sanctions for those who do not implement it.